2014
DOI: 10.4317/medoral.19683
|View full text |Cite
|
Sign up to set email alerts
|

Verrucous carcinoma of the oral mucosa: An epidemiological and follow-up study of patients treated with surgery in 5 last years

Abstract: Introduction: Oral Verrucous Carcinoma (OVC) is described apart of the Squamous Cell Carcinoma (SCC) due to its specific properties. The objective of our study is to show our series of cases of OVC and to compare with the SCC in terms of clinical manifestations, epidemiology, histopathology, treatment and follow-up. Material and Methods: This is a retrospective study of all the OVC treated in our department between January-2007 and December-2011. The analyzed variables were sex, age, localization in the oral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 22 publications
4
39
1
Order By: Relevance
“…In this study, the mean age of patients with verrucous carcinoma was reported as 64.13 years, which was similar to results in a study by Candau-Alvarez et al (24). Budimir et al (26) reported the mean age of patients with lichen planus as 67.23 years that is somewhat older than patients of OLP in present study (44.65), because most patients in Richter et al study were in 5th or 6th decade of their life.…”
Section: Agesupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, the mean age of patients with verrucous carcinoma was reported as 64.13 years, which was similar to results in a study by Candau-Alvarez et al (24). Budimir et al (26) reported the mean age of patients with lichen planus as 67.23 years that is somewhat older than patients of OLP in present study (44.65), because most patients in Richter et al study were in 5th or 6th decade of their life.…”
Section: Agesupporting
confidence: 91%
“…But also in recent decades the growing tendency of women to consumption of alcohol and cigarettes throughout the world leads to a reduction of male to female ratio in oral cancer (3). (10) 1 (5) 8 (40) 3 (15) 5 ( Our results regarding the verrucous carcinoma samples showed high prevalence in men (57.9%) compared to women (42.11%) in this group of the lesions, which is inconsistent with the findings of Candau-Alvarez et al (24).…”
Section: Sexcontrasting
confidence: 82%
See 1 more Smart Citation
“…Incomplete or excessive resection often accelerates tumor growth, leading to anaplastic transformation, poor function and difficult reconstruction. In this case, surgery (e.g., primary tumor resection and neck dissection) combined with radiotherapy and chemotherapy may be appropriate to minimize tumor recurrence and undesired prognosis (88)(89)(90). Table II shows the uses of surgery for OVC since mid-1980s, clearly demonstrating its effectiveness after treatment (91-94).…”
Section: Treatmentmentioning
confidence: 99%
“…Despite the scarcity of studies, principles regarding the general management of VC have been widely adopted and practiced by oncologic surgeons. For instance, the primary tumor site does not appear to influence management because surgery remains the primary treatment modality . Earlier studies endorsed management with primary radiation therapy; however, this fell out of favor due to groups reporting anaplastic transformation of lesions following treatment .…”
Section: Introductionmentioning
confidence: 99%